PERAN ORANG TUA ASUH DALAM MENANAMKAN AKIDAH AKHLAK ISLAM PADA SANTRI KELAS V MADRASAH IBTIDAIYAH DI ASRAMA PERSAHABATAN MAHAD AL-ZAYTUN - Sugeng Mariadi; Abdur Rahim (Bajang Institute, 2022)
This study aims to determine the role of foster parents towards MI early childhood in instilling Islamic morals in the fifth grade students of Madrasah Ibtidaiyah in the Mahad Al-Zaytun Friendship Dormitory. This study examines the role of foster parents for early childhood in improving Islamic morals and morals in fifth grade students at the Mahad Al-Zaytun Friendship Dormitory. This research method uses qualitative descriptive by using a naturalistic qualitative approach. The object of this research is the Caretaker of Class V MI Al-Zaytun students. The data sources of this research use primary data and secondary data. Research procedures or data collection techniques using observation, interviews and documentation. The results of the study revealed that the role of foster parents in the Friendship Dormitory of class V greatly influences the creation and implementation of activities or schedules given by management 130. In addition, the presence of caregivers also greatly affects the discipline, as well as orderliness of students in the Mahad Al-zaytun friendship dormitory.